Primeiro relato de atividade patogênica de Hirsutella thompsonii (Fischer) sobre o ácaro-da-erinose-da-lichia Aceria litchii (Keifer) - Picoli, Pedro Renan Ferreira [UNESP]; Vieira, Marineide Rosa [UNESP] (Universidade Estadual de Londrina, 2013)
The litchi erineum mite, Aceria litchii (Keifer) is found in all producing regions attacking leaves and flowers of litchi plants. The mite attack young leaves and causes the erinea on leaf surface, which later become brown galls with velvety appearance. Severe attacks can cause leaf drop and destruction of branches end directly production affecting. In 2009 year it was registered a heavy infestation of the pest on litchi plants (Litchi chinensis Sonn.) in the municipality of Casa Branca, São Paulo, Brazil (2127'O; 4702'S; 679 m altitude). In June, many galls caused by mite infestation showed a mycelium of white coloration and many eriophyid dead. The fungus was identified as Hirsutella thompsonii (Fischer). The results suggest that galls may facilitate the fungus development and its permanence on the plants. Thus, the possibility of mite biological control with H. thompsonii should be investigated.
First report of pathogenic activity of Hirsutella thompsonii (Fischer) on the litchi erineum mite Aceria litchii (Keifer)
Keywords: Acari; Biological control; Erinose; Litchi chinensis